¿Los acuerdos comerciales diversifican las exportaciones? El caso chileno - Da Ponte, Iván Nicolás (Latin American Journal of Trade Policy, 2021)
The general purpose of this paper is to answer the following question: What is the relationship between the number of trade agreements signed by Chile and its resulting export diversification/concentration? And is this relationship significant? To achieve this, we will analyze the relationship between four export diversification indicators (Gini, Hirschman-Herfindahl, Theil indices and the quantity of exported products) and trade agreements, controlling for the international price of copper, Chile’s real exchange rate and years of schooling -as a proxy for human capital-, using the Ordinary Least Squares method (OLS) in a multivariate regression analysis. The hypothesis that guides this study is that trade agreements in a general sense tend significantly to diversify exports, even when controlling for the concentrating effect of the international price of copper. However, and as it has been observed over the last thirty years, this effect has not been sufficient to produce a structural change on Chile’s export basket.